The Darwin Awards: sex differences in idiotic behaviour. (11th December 2014) - Lendrem, Ben Alexander Daniel; Lendrem, Dennis William; Gray, Andy; Isaacs, John Dudley
Abstract : Sex differences in risk seeking behaviour, emergency hospital admissions, and mortality are well documented. However, little is known about sex differences in idiotic risk taking behaviour. This paper reviews the data on winners of the Darwin Award over a 20 year period (1995-2014). Winners of the Darwin Award must eliminate themselves from the gene pool in such an idiotic manner that their action ensures one less idiot will survive. This paper reports a marked sex difference in Darwin Award winners: males are significantly more likely to receive the award than females (P<0.0001). We discuss some of the reasons for this difference.